2012
DOI: 10.1590/s0100-879x2012007500150
|View full text |Cite
|
Sign up to set email alerts
|

Oculo-facio-cardio-dental syndrome in three succeeding generations: genotypic data and phenotypic features

Abstract: Oculo-facio-cardio-dental (OFCD) syndrome is a rare X-linked disorder mainly manifesting in females. Patients show ocular, facial, cardiac, and dental abnormalities. OFCD syndrome is caused by heterozygous mutations in the BCOR gene, located in Xp11.4, encoding the BCL6 co-repressor. We report a Croatian family with four female members (grandmother, mother and monozygotic female twins) diagnosed with OFCD syndrome who carry the novel BCOR mutation c.4438C>T (p.R1480*). They present high intrafamilial phenotypi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…The reported mutations were dispersed along the entire 15 exons of the BCOR gene and most of these mutations were predicted to generate premature stop codons (PTCs). Regardless of the mutation site, all patients have similar typical OFCD phenotypes, but differ in severity even in single families with the same mutation[8].…”
Section: Introductionmentioning
confidence: 96%
“…The reported mutations were dispersed along the entire 15 exons of the BCOR gene and most of these mutations were predicted to generate premature stop codons (PTCs). Regardless of the mutation site, all patients have similar typical OFCD phenotypes, but differ in severity even in single families with the same mutation[8].…”
Section: Introductionmentioning
confidence: 96%
“…The infant shows square face, broad forehead, eyebrows laterally extended and horizontal, and wide nasal bridge with broad nasal tip and deep. The phenotypic difference between adult and infant is important in syndromic conditions with mild phenotype in younger patients (Lozić et al, 2012). Moreover, the most important criteria for the diagnosis of oculo-facio-cardio-dental syndrome are dental anomalies, in particular extreme elongation of the cuspids' roots, but only in permanent dentition.…”
Section: Resultsmentioning
confidence: 99%
“…The protein selectively interacts with the POZ domain of BCL6. BCOR is expressed in many tissues, including the eyes, teeth, and the nerve canal, and plays an important role in the regulation of early embryo development (Lozic et al, 2012).…”
Section: Oculo-facio-cardio-dental Syndromementioning
confidence: 99%
“…Lozic et al (2012) reported a new heterozygous mutation, c.4438C>T (p.R1480*), in exon 11 of BCOR in identical twins with oculo-facio-cardio-dental syndrome by short tandem repeat analysis and sequencing. Danda et al (2014) identified a novel mutation in exon 7 of BCOR, c.3490C>T (p.R1164*), in two Indian sisters with oculo-faciocardio-dental syndrome, via sequencing.…”
Section: Oculo-facio-cardio-dental Syndromementioning
confidence: 99%